Paediatric arrhythmias in the emergency department - Clausen, Henning ; 0000-0003-3373-5786; Theophilos, Theane; Jackno, Kim; Babl, Franz E. (Emergency Medicine Journal, 2012)
Objective: Emergency department (ED) staff need to rapidly establish accurate diagnosis and management for children with arrhythmias. Limited data are available on the presenting features, epidemiology and management of arrhythmias encountered in the ED. The aim of this study was to characterise the incidence, presenting features, management and outcomes of arrhythmias at a large tertiary children's hospital ED. Patients and methods: Retrospective review of medical records identified via the ED electronic database using ICD-10 codes for arrhythmias including cardiac arrests over a 6-year period (2002-2008). Patients <18 years were analysed using predefined criteria. Results: There were a total of 444 non-arrest arrhythmias with an incidence of 11.5:10 000 presentations. Median age of patients at presentation was 10.4 years; 45% were male. Supraventricular arrhythmias (SVTs) represented the largest subgroup (n=250, 56%). Conduction disorders (n=18), ventricular tachycardia (n=17) and atrial flutter/fibrillation (n=7) were rare. There were 19 cardiac arrests. Fifty-seven (13%) patients had underlying congenital heart disease. For ongoing SVT (n=135), vagal manoeuvres were used in 74%, and antiarrhythmic drugs in 64%. In five patients with SVT, drugs other than adenosine were used. Defibrillators were used only on 2 occasions for arrthymias and 6 times for cardiac arrests. 18 of 19 children in cardiac arrest died. Conclusion: In this largest paediatric series outside the intensive care and postoperative setting, arrhythmias were uncommon, defibrillator use was very rare, and observed mortality was low.